An Unusual Case Report of Tetanus with Convulsion and Breathlessness in Child - Jha, Deepak; Rathod, Dipali; Akbar, Md; Shaikh, Ayaz (Indian Journal of Pharmacy Practice)
Tetanus is an uncommon, severe infection that poses a life-threatening risk and is primarily caused by the bacterium Clostridium tetani. In this case report, we present the clinical manifestation of tetanus in a 6-year-old boy, which includes symptoms such as fever, jaw and neck muscle contraction, convulsions, and difficulty in breathing. The patient was treated with a combination of tetanus immunoglobulin, antibiotics, antipyretics, and sedatives. Laboratory investigations unveiled an increased white blood cell count with a normocytic, hypochromic blood profile with neutrophilia. The patient recovered successfully after 10 days of hospitalization. This case report highlights the significance of tetanus vaccination and the crucial role of prompt management of tetanus, and if left untreated can lead to severe complications and death.
Keywords: Tetanus; Convulsion; Breathlessness; Child; Life-threatening